Lung and gallbladder cancer survival in north India: an ambidirectional feasibility cohort study using telephone interviews - Krithiga Shridhar; Rakesh Kapoor; Michael Goodman; Dimple Kondal; Kavita Narang; Preeti Singh; Jarnail S Thakur; Preet K Dhillon (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background We report the feasibility of using telephones for active surveillance of cancer survival and also present absolute survival rate and its predictors for lung cancer (LC) and gallbladder cancer (GBC) in north India. To date, such information from resource intensive settings is limited. # Methods Study participants were 530 men and women (259 LC and 271 GBC), registered at 'Post Graduate Institute of Medical Education and Research', Chandigarh. Eligible patients were diagnosed with LC or GBC between ages 30 and 69 years during a five-year period from January 1 2010 through December 31 2014, and had a valid telephone number. Information on socio-demographic factors, disease characteristics and treatment status was abstracted from medical records. Participants (or their family/relatives) were followed-up with telephone interviews (March 1 2016 to July 31 2016) to ascertain vital status. Absolute 1-, 3- and 5-year survival rates were calculated using Kaplan-Meier method; weighted Cox Proportional Hazards regression multivariable models were used to evaluate determinants of survival while accounting for losses to follow up. # Results Over two-thirds of the participants or their families (66.7%) were successfully followed-up via telephone calls. Survival analysis included 354 participants (N=175 LC; 179 GBC) with 326 deaths observed during follow up (N=158 LC; 168 GBC). Absolute survival rates (expressed as percentages with 95% confidence intervals) for LC were 36.7 (29.5-44.7), 10.2 (6.1-15.6) and 2.1 (0.2-8.1) and for GBC 29.0 (22.6-35.8), 5.4 (2.5-9.8) and nil for 1-year, 3-years and 5-years post-diagnosis, respectively; GBC had lower survival rates than LC (P=0.049). Pre-treatment clinical extent of disease was the only significant predictor of survival rates especially for GBC. # Conclusions Active follow-up of cancer patients through telephone calls is feasible and acceptable in India. Poor survival rates of both LC and GBC underscore the importance of active surveillance by reaching out to family members through practically feasible methods.